Captured by Evil - LAURA S. UNDERKUFFLER (Yale University Press, 2013)
The subject of this book is corruption. â€œCorruptionâ€ is one of the most powerful words in the English language. When (for instance) we think of corruption of food, human bodies, or other physical objects, we think of something that is fundamentally or revoltingly altered, impure, rotten, or worse. When we think of corruption in governmentâ€”the subject of this bookâ€”the impact of this word is equally powerful. Charges of corruption in public life have condemned men, destroyed the lives of women, and accelerated the decline and fall of governments. Corruption is something that human beings instinctively loathe, and that we try to excise from our midst. The word itself conjures something that is powerful, insidious, and destructive of human lives and institutions. The thesis of this book is that corruption, when used in law, is a troubled concept. The contemporary Western ideology of law assumes that law must operate within a universe of knowable and articulable standards, logical and demystified, that strive toward neutral content and operation. Corruption, I shall argue defies these limits. It is, in its essence, a pre-Enlightenment, intuitive, and emotional concept that relies on â€œreligiouslyâ€ revealed ideas of good and evil, falsity and truth. It is, in philosophical terms, a â€œdegenerateâ€ or â€œincommensurableâ€ concept. It contradicts the dominant theory or â€œway of knowingâ€ of law, and is something which that dominant theory cannot explain.